The beauty of continuous development of the nurse as the beauty of nursing as an art - Pucko, Zygmunt; Przybek-Mita, Joanna (Nursing in the 21st Century, 2021)
THE BEAUTY OF CONTINUOUS DEVELOPMENT OF THE NURSE AS THE BEAUTY OF NURSING AS AN ART Introduction. Looking from a philosophical perspective at the continuous process of the nurse’s education, one can see in it a dimension that has not yet been brought to light. Meanwhile, it gives the nurse greater splendour and respect. It also changes the perception of the nurse in collective consciousness and creates her new image in the cultural code. This aspect is beauty, which also defines nursing understood as an art. The theoretical frame of this consideration is the concept of aesthetics of Cyprian Kamil Norwid. His approach determines the aesthetic shade of the nurse’s continuous development and legitimizes the aesthetic status of such thought categories as e.g. dynamism, purposefulness, proportionality, depth, originality, complementation, rigor or asceticism. It also authorizes the identification of nursing with art and opens the door for contemporary explanations of such identification. Aim. To show the beauty of the continuous development of the nurse. Indication of the constitutive features of the beauty of continuous learning. An attempt to justify giving nursing the title of an art. Method. Phenomenological method. This method was developed by Edmund Husserl and consists in viewing and describing a phenomenon or an object given to the researcher by eye. The purpose of this method is to get to the essence of the cognitively understood object and to recognize it clearly and distinctly. Capturing the quintessence of a phenomenon or an object is achieved through phenomenological reduction, meaning presuppositionlessness in the research approach and the so-called eidetic view. Conclusions. The permanent continuum of the nurse’s development process has an aesthetic value. Nursing has been elevated to the rank of art for several decades. The introduction of nursing to the pantheon of art is proved from various points of view. Nursing understood as an art does not yet have a consistent theory or precise conceptual grid. Based on the resultant of many arguments, this ennoblement of nursing is difficult to challenge.